THE CORRELATION BETWEEN PATIENT SATISFACTION AND PEOPLE EQUITY AMONG PARAMEDIC STAFFS IN INPATIENT ROOMS - Sendhi Tristanti Puspitasari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: One of the elements controlling the quality of hospital health services is patient and employee satisfaction. The mean value of patient satisfaction with all parameters of inpatient rooms at the Islamic Hospital in Surabaya from January to August 2016 was 61.3% which is less than the standard of ≥ 90%. Whereas, people equity is a concept of human resource management that signs organizational performance.Aims: This study examined the correlation between patient satisfaction and people equity among paramedic staffs especially in inpatient rooms of the Islamic Hospital in Surabaya.Methods: This study focused on measuring people equity, patient satisfaction, and the correlation between people satisfaction and people equity. The questionnaire used in this study adopted RATER dimensions (Reliability, Assurance, Tangible, Empathy, and Responsiveness).Results: The study found that three inpatient rooms (Muzdalifah, Arofah, and Shofa) did not meet three elements of people equity (Alignment, Capabilities, and Engagement). Patient satisfaction with the inpatient rooms was good, except for the tangible dimension especially room cleanliness which is still relatively low. People equity among the paramedic staff has strong relevance and is directly proportional to patient satisfaction with the inpatient rooms of the Islamic Hospital in Surabaya.Conclusion: Internalizing an organizational culture that considers patient satisfaction and patient equity among paramedic staffs is essential to harmonize the goals, vision, and mission between the hospital and its staffs. This study recommends that there should be a more serious evaluation of the cleanliness of all service units at the Islamic Hospital in Surabaya.Keywords: Patient satisfaction, People equity, Human Resource Management, Service performance.